Molybdenum-Catalyzed (E)-Selective Anti-Markovnikov Hydrosilylation of Alkynes - Feihua Ye; Zhaoyang Huang; Jiahao Li; Qiumin Wang; Lihuan Wu; Xiang Li (Molecules, 2024)
Herein, we report the first example of molybdenum-catalyzed (E)-Selective anti-Markovnikov hydrosilylation of alkynes. The reaction operates effectively with the utilization of minute amounts of the inexpensive, bench-stable pre-catalyst and ligand under mild conditions. Moreover, this molybdenum-catalyzed hydrosilylation process features the advantages of simple operation, excellent selectivity, and broad functional groups tolerance.